Analysis of Public Service Quality at the Department of Population and Civil Registration Using the Go Digital Application in West Lombok - Gagam Sarwadi; Rossi Maunofa Widayat; Inka Nusamuda Pratama (CV. Era Digital Nusantara, 2026)
This study analyzes the quality of public services delivered by the Population and Civil Registration Office of West Lombok Regency through the Go Digital application and identifies the main barriers that still limit its optimization. The study is important because population administration services are directly linked to citizens' legal identity and daily access to other public services, while digital transformation has become a strategic direction of Indonesian public administration. A descriptive qualitative case-study design was used. Data were collected through in-depth interviews, observation, and documentation involving three key informants: the head of population administration information management, the Go Digital service operator, and community members who used the service. Data were analyzed inductively through reduction, display, and conclusion drawing with SERVQUAL as the analytical framework, covering reliability, responsiveness, assurance, empathy, and tangibles. The findings show that Go Digital has improved service quality by making procedures more structured, reducing queues, shortening processing time, increasing transparency, and widening access to administrative services. The application also supports better document tracking and reduces informal brokerage practices. However, service optimization is still constrained by unstable internet networks, system disruptions, fluctuating service responsiveness during peak demand, and limited digital literacy among some citizens. The study concludes that Go Digital has contributed positively to the modernization of public services at Disdukcapil West Lombok, but sustainable improvement requires stronger infrastructure, better system stability, continuous public education, and more intensive assistance for digitally vulnerable users.